Parametrization of Mean Radiative Properties of Optically Thin Steady-State Plasmas and Applications (Communications in Computational Physics, 2014)
Plasma radiative properties play a pivotal role both in nuclear fusion and astrophysics. They are essential to analyze and explain experiments or observations andalso in radiative-hydrodynamics simulations. Their computation requires the generation of large atomic databases and the calculation, by solving a set of rate equations, ofa huge number of atomic level populations in wide ranges of plasma conditions. Thesefacts make that, for example, radiative-hydrodynamics in-line simulations be almostinfeasible. This has lead to develop analytical expressions based on the parametrization of radiative properties. However, most of them are accurate only for coronal orlocal thermodynamic equilibrium. In this work we present a code for the parametrization of plasma radiative properties of mono-component plasmas, in terms of plasmadensity and temperature, such as radiative power loss, the Planck and Rosseland meanopacities and the average ionization, which is valid for steady-state optically thin plasmas in wide ranges of plasma densities and temperatures. Furthermore, we alsopresent some applications of this parametrization such as the analysis of the opticaldepth and radiative character of plasmas, the use to perform diagnostics of the electron temperature, the determination of mean radiative properties for multicomponentplasmas and the analysis of radiative cooling instabilities in some kind of experimentson high-energy density laboratory astrophysics. Finally, to ease the use of the codefor the parametrization, this one has been integrated in a user interface and brief comments about it are presented.